Cytochrome P450 2J2: distribution, function, regulation, genetic polymorphisms and clinical significance. (18th July 2013) - Xu, Meijuan; Ju, Wenzheng; Hao, Haiping; Wang, Guangji; Li, Ping
Abstract: Cytochrome P450 2J2 (CYP2J2) is an enzyme mainly found in human extrahepatic tissues, with predominant expression in the cardiovascular systems and lower levels in the intestine, kidney, lung, pancreas, brain, liver, etc. During the past 15 years, CYP2J2 has attracted much attention for its epoxygenase activity in arachidonic acid (AA) metabolism. It converts AA to four epoxyeicosatrienoic acids (EETs) that have various biological effects, especially in the cardiovascular systems. In recent publications, CYP2J2 is shown highly expressed in various human tumor cells, and its EET metabolites are demonstrated to implicate in the pathologic development of human cancers. CYP2J2 is also a human CYP that involved in phase I xenobiotics metabolism. Antihistamine drugs and many other compounds were identified as the substrates of CYP2J2, and studies have demonstrated that these substrates have a broad structural diversity. CYP2J2 is found not readily induced by known P450 inducers; however, its expression could be regulated in some pathological conditions, might through the activator protein-1(AP-1), the AP-1-like element and microRNA let-7b. Several genetic mutations in the CYP2J2 gene have been identified in humans, and some of them have been shown to have potential associations with some diseases. With the increasing awareness of its roles in cancer disease and drug metabolism, studies about CYP2J2 are still going on, and various inhibitors of CYP2J2 have been determined. Further studies are needed to delineate the roles of CYP2J2 in disease pathology, drug development and clinical practice.